STATISTICAL TEST FOR INTERACTION OF GXE ON QPM GRAIN YELLOW FOR HYBRID CANDIDATE UNDER LOWLAND IN INDONESIA - HG, M Yasin; La Sumange, La Sumange; Ruhumuddin, Ruhumuddin; Jamaluddin, Jamaluddin; Isnaeni, Musdalifah; Faesal, Faesal (Insan Cita : Jurnal Pengabdian Kepada Masyarakat, 2021)
The application of statitical test has been conducted on  interaction of two factors were ten genotypes as single crosses (G) and  five environments (E) under QPM grain yellow for candidate of releasing new hybrid by iceri Maros. Statistical pooled model were (1) yi= µ+τ+α+ε and (2) yij=µ+τ/ƛ+α+(αxƛ)+ε, (effect of mean, replication within location, entri, interaction gxe, error).  The parent material was introduced of CIMMYT Maize Lines (CML) and tester grain yellow color was modified by MR14xCML164 in backcrosses untill BC3F3. The environemt (ei, i=1,2,3, 4,5) were  lowland zone in (e1)Maros experimental Farm, (e2)Bajeng, (e3)Bontobili, (e4)Sidondo and (e5)Polman farmers field. Experiments were conducted by RBD with three replications. The first analyzed were separate in each ei (i:1,2,3,4,5), and contuining in pool analyzed by gj (j:1,2,3, . . . , 10), there are ten variables were observed and grain yield be predicted in wc. 15%. Spacing by used 75x20cm one plant per se, fertilizer be applied urea-ponska (200-150) kg/ha, weeding and irrigated was regularly conducted for max.plant growth. The experiments conducted as evt on rainy season 2018. Statistical test shown that there are siginificant differet of genotypes under five environments, interaction gxe, and cv: 10.69%, test by lsd (least significant different) founded two candidates single cross (1)CML161-2-1-4-2xMR14Q and (2)CML165-3-1-2-4xMR14Q were highly yield and significant different with two check MSQ.C0xMR14Q and Bima 13Q. The two single crosses could be promising as new QPM hybrids with yield  potential 9.0-10.0 t/ha, characters ear position was middle of plant height, shelling 75.2-77.8%, flowering 55 days and plant aspect be score one (very nice).QPM (Quality Protein Maize/Corn) is material which is difine specialty corn which  high content of  lysine and tryptophane. These are two essential amino acids better nutritional for human body, anticipated  of disease (kwashiorkor) on severe among children, and could be corrective use in balancing diets.Key words : QPM, single cross, pooled analyzed